Does Watching a Monkey Change its Behaviour? Quantifying Observer Effects in Habituated Wild Primates using Automated Radiotelemetry - M. C. Crofoot; Lambert, T. D.; R. W. Kays; M. Wikelski (Animal Behaviour, 2010)
In studies of animal behaviour, researchers have long been concerned that their presence may change the conduct of their study subjects. To minimize observer effects, researchers often habituate their study animals. The premise of this method is that, with sufficient neutral exposure, animals will stop reacting to humans. While numerous studies demonstrate that negative responses to humans decrease over time, the fact that an animal does not flee from or behave aggressively towards observers cannot be taken as evidence that it is not altering its behaviour in other, more subtle ways. Because remotely monitoring the behaviour of wild animals is difficult, it has not been possible to answer the critical question: do habituated animals change their behaviour when researchers are present? Here, we use data from an automated radiotelemetry system that remotely monitored the movement and activity of radiocollared animals to test whether observers affected the behaviour of seven habituated white-faced capuchins, Cebus capucinus. We found no evidence that observers influenced the ranging behaviour or activity patterns of their study subjects. Capuchins did not move faster, stop to rest less frequently, or display higher levels of activity when they were being followed compared to when they were alone. It has been suggested that researchers may embolden habituated study subjects, artificially increasing their relative dominance, but we found no relationship between observer presence and proximity to neighbouring social groups. Although it remains possible that observer effects existed but were too subtle to be detected with the remote sensing technology we used, the results of this study nevertheless provide reassuring evidence that humans can observe habituated wild animals without overly influencing the animals’ activity and movement patterns.
Keywords: Barro Colorado Island; Panama; Cebus capucinus; habituation; telemetry

Interaction Location Outweighs the Competitive Advantage of Numerical Superiority in Cebus capucinus Intergroup Contests - M. C. Crofoot; Gilby, I. C.; M. Wikelski; R. W. Kays (Proceedings of the National Academy of Sciences, 2008)
Numerical superiority confers a competitive advantage during contests among animal groups, shaping patterns of resource access, and, by extension, fitness. However, relative group size does not always determine the winner of intergroup contests. Smaller, presumably weaker social groups often defeat their larger neighbors, but how and when they are able to do so remains poorly understood. Models of competition between individuals suggest that location may influence contest outcome. However, because of the logistical difficulties of studying intergroup interactions, previous studies have been unable to determine how contest location and group size interact to shape relationships among groups. We address this question by using an automated radio telemetry system to study intergroup interactions among six capuchin monkey (Cebus capucinus) social groups of varying sizes. We find that the odds of winning increase with relative group size; one additional group member increases the odds of winning an interaction by 10%. However, this effect is not uniform across space; with each 100 m that a group moves away from the center of its home range, its odds of winning an interaction decrease by 31%. We demonstrate that contest outcome depends on an interaction between group size and location, such that small groups can defeat much larger groups near the center of their home range. The tendency of resident groups to win contests may help explain how small groups persist in areas with intense intergroup competition.
Keywords: between-group competition; intergroup dominance; payoff asymmetries; resource holding potential